Improving head growth in preterm infants – a randomised controlled trial II: MRI and developmental outcomes in the first year. Issue 5 (19th February 2008) - Tan, M; Abernethy, L; Cooke, R
Abstract : Background: Very preterm infants are at risk of poor growth and neurodevelopmental outcome. Illness and difficulties overcoming the challenges of feeding these infants often lead to undernutrition in the first few weeks. Objective: To explore the relationships between early nutrition, post-natal head growth, quantitative magnetic resonance imaging (MRI) and developmental outcome in the first year among infants born before 29 weeks' gestation. Design: Infants born before 29 weeks' gestation were randomised to receive hyperalimented or standard feeding regimen from birth to 34 weeks' postmenstrual age (PMA). The primary outcome was occipitofrontal circumference (OFC) at 36 weeks' OFC. Quantitative MRI was performed at 40 weeks' PMA. Developmental assessment using Bayley Scales of Infant Development II (BSID II) was carried out at 3 and 9 months post-term. Results: 109 infants survived to the end of the first year PMA. 65 infants underwent MRI scan. 81 and 71 infants were seen at 3 and 9 months post-term. Quantitative MRI findings, mental development index (MDI) and psychomotor development index (PDI) were not statistically different between the two groups. Total brain volume (TBV) at 40 weeks' PMA, MDI and PDI at 3 months post-term correlated significantly with energy deficit at 28 days of age Conclusions: Improving early energy deficit in very preterm infants may promote brain growth. Quantitative MRI may have a role to play in predicting developmental outcome. Post-natal growth at 36 weeks' PMA and quantitative MRI finding at 40 weeks' PMA appear to be closely related to mental outcomes in the first year. Trial registration number: ISRCTN 19509258